A method for preparing a germanium-based composite material with high photoelectric response
By doping antimony or tellurium into the germanium-based composite material and adjusting the electronic structure, the problem of electron fallback under GeH photoexcitation is solved, and the gain effect of high photoelectric response performance is achieved.
Patent Information
- Application Number
- CN202410635260.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-05-22
AI Technical Summary
Hydrogen-capped germanene (GeH) electron fallback under light excitation results in a high recombination rate of photogenerated electron-hole pairs, hindering its practical application.
By doping antimony or tellurium into the germanium-based composite material, adjust its electronic structure, broaden the spectral response range of the detector, and improve photoelectric performance. Specific steps include mixing calcining, acid reaction, etc. to form Sb-GeH or Te-GeH composite material.
The adjustment of GeH electronic structure is achieved, and the recombination of photogenerated carriers is regulated, thereby improving its photoelectric performance, extending the life of carriers, and improving the separation efficiency of carriers.
Smart Images

Figure CN118222868B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photoelectric detection technology, and in particular to a method for preparing a germanium-based composite material with high photoelectric response. Background Art
[0002] Photodetectors have increasingly wide applications in civil and defense fields, such as optical communications, imaging, and missile monitoring, which has led to increasing attention for photodetectors. Two-dimensional (2D) semiconductor materials have great prospects in the field of optoelectronics due to their unique optical and electrical properties. Experiments and theories have proven that some photodetectors based on 2D materials have high responsivity, high detection rate, good response speed, tunable response spectrum, and good stability. Photoelectric materials are the core of photodetectors. Each material has its own unique properties and can be used in photodetectors of different wavelengths. Therefore, it is particularly important to study the photoelectric materials in photodetectors.
[0003] Germanene is a member of the graphene family. p 2 and p 3 Hybridized germanium atoms have become a major contender in two-dimensional materials due to their strong spin-orbit coupling and intrinsically low-buckling structure, which provide the opportunity to open an energy band gap in the electronic band structure. Germanene has a large spin-orbit gap (24 meV), tunable band structure, high carrier mobility, and quantum Hall effect, making it a promising material for electronics and optoelectronics.
[0004] Hydrogen-terminated germanene (GeH) not only has high carrier mobility similar to germanene, but also has strong light-matter interaction with a direct band gap. In addition, two-dimensional germanene is also a good candidate material for electronic devices due to its high aspect ratio and ductility. Despite these superior properties, GeH also has some disadvantages: the valence band top (VBM) is mainly composed of Ge 4 p orbitals, while the conduction band bottom (CBM) is composed of Ge 4 s and 4 p In the mixed-state composition, the charge density distributions of VBM and CBM overlap to a large extent, so under photoexcitation, electrons are likely to fall back to the valence band, resulting in a high recombination rate of photogenerated electron-hole pairs, thus hindering the practical application of GeH.
[0005] Research has found that the band gap of hydrogen-terminated germanene (GeH) can be adjusted by doping, surface modification, and heterostructure construction, aiming to broaden the spectral response range of the detector and improve the photoelectric performance of the detector. Therefore, it is important to select doping materials with equivalent band positions and electronic structures, and they can serve as collectors of photogenerated electrons and holes. GeH is a photoelectric detection material with broad application prospects and excellent performance. By doping and constructing heterojunctions, the photoelectric response performance and application range of GeH can be further expanded. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a germanium-based composite material with high photoelectric response, so as to solve the problems existing in the above-mentioned prior art and achieve an excellent gain effect of high photoelectric response.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] One of the technical solutions of the present invention is to provide a method for preparing a germanium-based composite material, comprising the following steps:
[0009] The germanium element, the calcium element and the solid element are mixed and calcined, and then cooled to obtain a calcined product;
[0010] Mixing the calcined product with an acid for reaction to obtain the germanium-based composite material;
[0011] The solid single substance is antimony or tellurium.
[0012] As a further preferred embodiment of the present invention, the mass ratio of the germanium element, the calcium element and the solid element is 1:0.5:0.5.
[0013] When the solid element is antimony, it is mixed and calcined to obtain CaGe2-Sb, which is mixed with acid to react to obtain Sb-GeH;
[0014] When the solid element is tellurium, CaGe2-Te is obtained by mixing and calcining; Te-GeH is obtained by mixing and reacting with acid.
[0015] Antimony and tellurium used in the present invention are both III-V main group elements, and their melting points are between germanium and calcium. During the calcination process, they can be doped in CaGe2, thereby changing the electronic state of GeH and adjusting its band gap width.
[0016] The present invention takes two-dimensional GeH as the research object, and adjusts the optical and electronic properties of the two-dimensional semiconductor by doping to enhance its photoelectric performance. Specifically, different elements (Sb or Te) are added to the precursor CaGe2 respectively, and then reacted with acid to obtain a composite material, which can achieve the adjustment of the electronic structure of GeH.
[0017] As a further preferred embodiment of the present invention, the calcination is vacuum calcination; the calcination temperature is 1000°C, and the calcination time is 24 hours. More preferably, during the calcination treatment, the temperature is increased to 1000°C at a heating rate of 3-5°C / min.
[0018] As a further preferred embodiment of the present invention, the cooling step is: cooling to 500°C at a cooling rate of 1-3°C / min, and then cooling to room temperature at a cooling rate of 2-4°C / min.
[0019] As a further preferred embodiment of the present invention, the temperature of the mixed reaction is -30°C, and the time of the mixed reaction is 48 h.
[0020] As a further preferred embodiment of the present invention, the acid is concentrated hydrochloric acid or hydrofluoric acid. More preferably, the mass concentration of the concentrated hydrochloric acid is 36%.
[0021] As a further preferred embodiment of the present invention, after the mixing reaction is completed, washing and ultrasonic steps are also included.
[0022] The second technical solution of the present invention is to provide a germanium-based composite material prepared by the above preparation method.
[0023] The third technical solution of the present invention is the application of the above-mentioned germanium-based composite material as a photoelectric response material.
[0024] A fourth technical solution of the present invention is to provide a photoelectric detector, comprising the above-mentioned germanene-based composite material.
[0025] As a further preference of the present invention, the germanium-based composite material is used as the photoanode, the platinum electrode is used as the counter electrode, the saturated calomel is used as the reference electrode, and the 0.5 M Na2SO4 aqueous solution is used as the electrolyte.
[0026] The present invention adjusts the electronic structure of GeH by bulk doping the precursor Zintl phase CaGe2 with SbTe, and then topologically deintercalating Sb-GeH and Te-GeH composites in a low-temperature acid environment. The obtained composite material can regulate the recombination of photogenerated carriers, thereby improving its photoelectric performance. At the same time, the constructed heterojunction can effectively prolong the life of carriers, thereby improving the separation efficiency of carriers.
[0027] The present invention discloses the following technical effects:
[0028] The invention prepares a germanium-based composite material with high photoelectric response, and the germanium-based composite material can be used as a photoelectric response material in a photoelectric detector.
[0029] The photoelectric detector based on the germanium-based composite material of the present invention has a high response value, a good detection rate and a fast response performance, and has great application prospects in optical signal detection and photoelectric signal conversion. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is the XRD diagram of the germanium-based composite material CaGe2-Sb obtained in Example 1.
[0032] Figure 2 This is the XRD pattern of the germanium-based composite material CaGe2-Sn obtained in Example 1.
[0033] Figure 3 This is the XRD diagram of the germanium-based composite material CaGe2-In obtained in Example 1.
[0034] Figure 4 This is the XRD pattern of the germanium-based composite material CaGe2-Te obtained in Example 1.
[0035] Figure 5 This is the XRD pattern of the germanene-based composite material Sb-GeH obtained in Example 1.
[0036] Figure 6 This is the XRD pattern of the germanene-based composite material Sn-GeH obtained in Example 1.
[0037] Figure 7 This is the XRD pattern of the germanene-based composite material In-GeH obtained in Example 1.
[0038] Figure 8 This is the XRD pattern of the germanene-based composite material Te-GeH obtained in Example 1.
[0039] Fig. 9 This is the SEM image of the germanium-based composite material Te-GeH obtained in Example 1.
[0040] Fig.10 This is the HRTEM image of the germanene-based composite material Te-GeH obtained in Example 1.
[0041] Fig.11 This is the Raman graph of the germanene-based composite material Te-GeH obtained in Example 1.
[0042] Fig.12This is the full XPS spectrum of the germanium-based composite material Te-GeH obtained in Example 1.
[0043] Fig.13 XPS Ge 3 of the germanium-based composite material Te-GeH obtained in Example 1 d picture.
[0044] Fig.14 The Sb-GeH-based photoelectrochemical photodetector and the GeH-based photoelectrochemical photodetector prepared in Example 2 were subjected to simulated sunlight (light intensity 60 mW / cm 2 )Comparison of time-current curves under irradiation.
[0045] Fig.15 The Sn-GeH-based photoelectrochemical photodetector and the GeH-based photoelectrochemical photodetector prepared in Example 2 were subjected to simulated sunlight (light intensity 60 mW / cm 2 )Comparison of time-current curves under irradiation.
[0046] Fig.16 The In-GeH-based photoelectrochemical photodetector prepared in Example 2 was subjected to simulated sunlight (light intensity 60 mW / cm 2 )Comparison of time-current curves under irradiation.
[0047] Fig.17 The Te-GeH-based photoelectrochemical photodetector prepared in Example 2 was subjected to simulated sunlight (light intensity 60 mW / cm 2 )Comparison of time-current curves under irradiation.
[0048] Fig.18 For Example 2, a Te-GeH-based photoelectrochemical photodetector was prepared to simulate sunlight (light intensity 60 mW / cm 2 ) Time-current curve captured under irradiation. DETAILED DESCRIPTION
[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0050] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0054] Example 1
[0055] Preparation of a germanium-based composite material:
[0056] S1. In an inert gas environment, germanium, calcium and solid were mixed in a mass ratio of 1:0.5:0.5 to obtain a mixture. Different mixtures were obtained according to the type of solid. The solid was antimony, tin, indium or tellurium. The four mixtures were ground and respectively loaded into four quartz tubes for vacuum sealing. The tubes were then placed in a muffle furnace and heated to 1000 °C at a heating rate of 4 °C / min and calcined for 24 h. After calcination, the tubes were first cooled to 500 °C at a cooling rate of 2 °C / min and then cooled to room temperature at a cooling rate of 2 °C / min to obtain CaGe2-Sb, CaGe2-Sn, CaGe2-In and CaGe2-Te crystals.
[0057] S2. The obtained CaGe2-Sb, CaGe2-Sn, CaGe2-In and CaGe2-Te crystals were transferred to round-bottom flasks respectively, and then 30 mL of concentrated hydrochloric acid (mass concentration of 36%) was added, followed by vacuum pumping to a vacuum state and stirring at -30°C for 48 h. In order to purify the product, after washing with deionized water and ethanol, the mixture was ultrasonically treated in an ice bath at 0°C for 30 min (power 200W). The obtained solution was centrifuged at 1000 rpm for 10 min to remove the unpeeled material. The supernatant containing the product was gently poured out, and then Sb-GeH, Sn-GeH, In-GeH and Te-GeH nanosheets were obtained after centrifugation at 10000 rpm for 10 min. Finally, the obtained material was stored in a vacuum drying oven at 60°C.
[0058] Comparative Example 1
[0059] Preparation of GeH:
[0060] The only difference from Example 1 is that no solid single substance is added in step S1.
[0061] CaGe2 is produced in step S1, and GeH is produced in step S2.
[0062] The XRD pattern of CaGe2-Sb obtained in Example 1 is as follows Figure 1 As shown, from Figure 1 As can be seen in the figure, almost all peaks correspond to the cubic phase of CaGe2 (PDF card number 13-0299), and the additional peaks can be attributed to Sb (PDF card number 17-0124). The presence of CaGe2 and Sb at the same time indicates the successful preparation of CaGe2-Sb.
[0063] The XRD pattern of CaGe2-Sn obtained in Example 1 is as follows Figure 2 As shown, almost all peaks correspond to the cubic phase of CaGe2 (PDF card number 13-0299), and the additional peaks can be attributed to Sn (PDF card number 04-0673). The presence of CaGe2 and Sn at the same time indicates the successful preparation of CaGe2-Sn.
[0064] The XRD pattern of CaGe2-In obtained in Example 1 is as follows Figure 3 As shown, almost all peaks correspond completely to the cubic phase of CaGe2 (PDF card number 13-0299), and the additional peaks can be attributed to In (PDF card number 05-0642). The presence of CaGe2 and In at the same time indicates the successful preparation of CaGe2-In.
[0065] The XRD pattern of CaGe2-Te obtained in Example 1 is as follows Figure 4As shown, almost all peaks correspond to the cubic phase of CaGe2 (PDF card number 13-0299), and the additional peaks can be attributed to Te (PDF card number 36-1452). The presence of CaGe2 and Te at the same time indicates the successful preparation of CaGe2-Te.
[0066] The XRD pattern of Sb-GeH obtained in Example 1 is as follows Figure 5 As shown, not only the diffraction peak of GeH but also the diffraction peak of Sb appeared, indicating the successful preparation of Sb-GeH.
[0067] The XRD pattern of Sn-GeH obtained in Example 1 is as follows Figure 6 As shown, not only the diffraction peak of GeH but also the diffraction peak of Sn appeared, indicating the successful preparation of Sn-GeH.
[0068] The XRD pattern of In-GeH obtained in Example 1 is as follows Figure 7 As shown, not only the diffraction peak of GeH but also the diffraction peak of In appeared, indicating the successful preparation of In-GeH.
[0069] The XRD pattern of Te-GeH obtained in Example 1 is as follows Figure 8 As shown, not only the diffraction peak of GeH but also the diffraction peak of Te appeared, indicating the successful preparation of Te-GeH.
[0070] Fig. 9 and Fig.10 Figures 9 and 10 are SEM and HRTEM images of the germanium-based composite material Te-GeH obtained in Example 1. As can be seen from Figure 9, the Te-GeH nanosheets show a few-layer sheet structure, indicating that a few-layer two-dimensional layered heterojunction Te-GeH is successfully peeled off from the bulk material. A fibrous cross-like structure also appears, and in Fig.10 This is also confirmed by the HRTEM image in the figure. The microstructure of Te-GeH nanosheets was studied using high-resolution transmission electron microscopy (HR-TEM). Through HRTEM, it can be seen that Te-GeH not only retains the original sheet morphology of GeH, but also has a highly interconnected fiber cross-shaped structure. By calculating the spacing of these fibrous structures, the d spacing is 3.23 Å, corresponding to the (101) plane of the Te structure. The successful synthesis of Te-GeH can be confirmed.
[0071] Fig.11 This is the Raman image of the germanium-based composite material Te-GeH obtained in Example 1. Raman measurement is an effective way to explore the structural characteristics of two-dimensional materials. At room temperature, the Raman spectrum was measured using a Raman microscope with an excitation laser wavelength of 532 nm. Fig.11 As shown, the E2 vibration of the Ge-H bond in GeH and the 280 cm-1 The relatively weak second-order peak is at about 240 cm -1 For the exfoliated Te-GeH nanosheets, two similar peaks are observed but with a slight blue shift, which may be attributed to the overlap of the above peaks. In addition, at about 430 cm -1 and 500 cm -1 Synchronous second-order absorption peaks were observed at
[0072] Fig.12 and Fig.13 The XPS spectrum of the Te-GeH composite material obtained in Example 1 and the Ge 3 d Figure. The full XPS spectrum shows the presence of Te and Ge. High resolution Ge 3 d like Fig.13 As shown, Ge 3 d The spectrum is mainly composed of four peaks, Ge-Ge at 29.84 eV, Ge-Te at 30.40 eV, Ge-H at 31.40 eV and Ge-O at 32.68 eV. The presence of Te doping in GeH further proves the successful preparation of Te-GeH.
[0073] Example 2
[0074] Preparation of photodetector:
[0075] 1 mg of the germanium-based composite material Te-GeH prepared in Example 1 was uniformly dispersed in 500 μL of ethanol, and after ultrasonic treatment, it was drop-coated on a cleaned ITO of 1 cm×2 cm in size. After drying, a photoanode was obtained. At the same time, a platinum electrode was used as a counter electrode, a saturated calomel was used as a reference electrode, and a 0.5 M Na2SO4 aqueous solution was used as an electrolyte to assemble a photoelectrochemical photodetector (Te-GeH-based photoelectrochemical photodetector). The simulated light intensity on the electrochemical workstation was 60 mW / cm 2 The photoelectric response performance was tested under 0 bias potential.
[0076] In the same way, GeH-based photoelectrochemical photodetectors, Sb-GeH-based photoelectrochemical photodetectors, Sn-GeH-based photoelectrochemical photodetectors and In-GeH-based photoelectrochemical photodetectors were prepared.
[0077] The Te-GeH-based photoelectrochemical photodetector prepared in Example 2 was tested by an electrochemical workstation to obtain a photocurrent density, and the photoresponsivity was calculated to be as high as 708.5 μA·W. -1 , detection rate up to 2.13×10 9 Jones, indicating that the material has high photoelectric response performance.
[0078] The calculation formula of light response is: R = I ph / P, where:
[0079] I ph is the photocurrent density, in μA·cm -2 ; P is the input power density, in mW / cm 2 (The power density tested in Example 2 is 60 mW / cm 2 ).
[0080] The calculation formula of detection rate (D) is: D = RS 1 / 2 / (2qI dark ) 1 / 2 , where:
[0081] R is the light response, in μA·W -1 ;
[0082] S is the area of the working electrode that is illuminated by light, in cm 2 ;
[0083] q is the electron charge, and its value is 1.602 × 10 -19 C;
[0084] I dark Indicates the current density under dark conditions, in μA cm -2 .
[0085] Figure 14-17 The Sb-GeH-based photoelectrochemical photodetector, Sn-GeH-based photoelectrochemical photodetector, In-GeH-based photoelectrochemical photodetector and Te-GeH-based photoelectrochemical photodetector prepared in Example 2 were respectively subjected to simulated sunlight (light intensity 60 mW / cm 2 )Comparison of time-current curves under irradiation.
[0086] It can be seen that Te-GeH has good photogenerated charge separation and migration properties. The photocurrent density of the Te-GeH composite material formed after Te doping is significantly improved, which is about 10 times that of GeH.
[0087] The photoelectrochemical photodetector of the photoanode prepared in Example 2 was placed under simulated sunlight (light intensity 60 mW / cm 2 ) irradiation, the light source was set to 5 seconds "on" and 5 seconds "off" in an alternating cycle to carry out the photoelectric response test.
[0088] Fig.18 The Te-GeH-based photoelectrochemical photodetector prepared in Example 2 was subjected to simulated sunlight (light intensity 60 mW / cm2 ) is used to obtain the time-current curve under irradiation, and the response rise time (t r ) and decay time (t d ). Response speed is an important factor in determining the practical application potential of photodetectors. r The definition of t is to describe the time interval from 10% to 90% of the response. d The definition of is to describe the time interval for the response to drop from 90% to 10%. After calculation, the t of the Te-GeH-based photoelectrochemical photodetector prepared in Example 2 is r =0.092 s, t d =0.526 s, showing a faster t r and t d , and its response speed is better than that of photoelectrochemical photodetectors.
[0089] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A photoelectric detector, characterized in that: It includes a germanium-based composite material, wherein the germanium-based composite material is used as a photoanode; The preparation method of the germanium-based composite material comprises the following steps: mixing and calcining a germanium element, a calcium element and a solid element, and then cooling to obtain a calcined product; mixing and reacting the calcined product with an acid to obtain the germanium-based composite material; The solid single substance is tellurium; the mass ratio of the germanium single substance, the calcium single substance and the solid single substance is 1:0.5:0.5; the calcination is vacuum calcination; the calcination temperature is 1000°C, and the calcination time is 24h; the cooling step is: cooling to 500°C at a cooling rate of 1-3°C / min, and then cooling to room temperature at a cooling rate of 2-4°C / min; the temperature of the mixed reaction is -30°C, and the mixing reaction time is 48h; the acid is concentrated hydrochloric acid or hydrofluoric acid; The germanium-based composite material is Te-GeH. In addition to retaining the original sheet-like morphology of GeH, the Te-GeH nanosheet also has a highly interconnected fiber cross-shaped structure.
Citation Information
Patent Citations
Two-dimensional layered tellurium-doped germane and preparation method thereof
CN112429703A
Two-dimensional layered heterojunction Ge-GeH, photoelectric anode material and preparation method of two-dimensional layered heterojunction Ge-GeH
CN113394023A